2020
DOI: 10.1097/sla.0000000000003640
|View full text |Cite
|
Sign up to set email alerts
|

Academic Partnerships in Global Surgery

Abstract: Most surgeons from high-income countries who work in global surgery will do so through partnerships between their institutions and institutions in low- and middle-income countries (LMICs). In this article, the American Surgical Association Working Group for Global Surgery lays out recommendations for criteria that contribute to equitable, sustainable, and effective partnerships. These include ethically engaging with the LMIC partner institution by putting its interests first and by proactively seeking to be aw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Alternatively, the International Bladder Exstrophy Consortium has worked to embody the guiding principles for ethical engagement in global surgery from the American Surgical Association Working Group on Academic Global Surgery 21 which include the following:…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the International Bladder Exstrophy Consortium has worked to embody the guiding principles for ethical engagement in global surgery from the American Surgical Association Working Group on Academic Global Surgery 21 which include the following:…”
Section: Discussionmentioning
confidence: 99%
“…Given the power differential between high-income countries’ partners and low-income and middle-income countries’ partners, it is recommended that, for research studies the ethics review board of the in low-income and middle-income countries’ institution and the institutional review board of the U.S. institution jointly approve how informed consent is obtained. 4 As with research studies, there is potential for ethical conflicts and misunderstandings to occur in relation to performing procedures and obtaining content that will be shared publicly. Thus, the recommendation for a collaborative approach to creating informed consent forms and protocols is also applicable in these scenarios to ensure mutual agreement in goals of the partnership and cultural sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns raised include the prioritization of the academic careers and research interests of high-income countries’ partners over the needs of low-income and middle-income countries’ partners 2,3 and misunderstandings and ethical conflicts regarding informed consent. 4 Furthermore, the increasing use of social media in surgery and global health has presented additional ethical challenges, including the protection of patient confidentiality. 5 According to guidelines outlined by the National Commission for the Protection of Human Subjects of Biomedical and Behavioral Research, informed consent must be obtained without coercion or undue influence and in the language of the consentee.…”
mentioning
confidence: 99%
“…Some pediatric and internal medicine residency programs have also developed exchange programs with LMIC partner institutions [68][69][70]. However, few surgical training programs have developed such exchange programs [49,[70][71][72][73][74][75]. A 2020 systematic review of surgical training partnerships between HIC and LMIC by Price et al found that only one partnership offered bidirectional exchange and only two offered South-to-North exchange.…”
Section: From Unidirectional Capacity Building To Bidirectional Exchangementioning
confidence: 99%